Phagosomal TLR signaling upon Borrelia burgdorferi infection - Cervantes, Jorge L.; Hawley, Kelly L.; Benjamin, Sarah J.; Weinerman, Bennett; Luu, Stephanie M.; Salazar, Juan C. (Frontiers in Cellular and Infection Microbiology, 2014)
Internalization and degradation of live Bb within phagosomal compartments of monocytes, macrophages and dendritic cells (DCs), allows for the release of lipoproteins, nucleic acids and other microbial products, triggering a broad and robust inflammatory response. Toll-like receptors (TLRs) are key players in the recognition of spirochetal ligands from whole viable organisms (i.e., vita-PAMPs). Herein we will review the role of endosomal TLRs in the response to the Lyme disease spirochete.